Raising Awareness of 3R (Reduce, Reuse, Recycle) Using Revin the Environment Hero Serious Game for Elementary Schoolers - Peter Jose; Remy Giovanny Mangowal; Andre; Mikhael Ming Khosasih; Vanessa Valencia Santoso (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
Indonesia faces a significant environmental challenge with rising annual waste production, reaching 69.7 million tonnes in 2023, yet only 62.91% was properly managed. This problem stems from a lack of awareness about proper waste management, especially among children. To address this issue, this study developed Revin the Environment Hero, a serious game designed to enhance elementary school students' understanding of the 3R concept (Reduce, Reuse, Recycle). Employing a Research & Development approach with the ADDIE model, the game was tested with 40 elementary students in Surabaya. Pre-test and post-test questionnaires assessed the game's effectiveness, and a Paired Sample T-Test showed a significant improvement in students' 3R knowledge (t-value = -12.637, p < 0.001). Feedback revealed high satisfaction with the game’s engaging narrative, interactive mechanics, and clear instructions. The game not only increased students’ theoretical knowledge but also encouraged practical application of the 3R principles through creative recycling activities. These findings demonstrate the potential of serious games as effective educational tools for promoting environmental awareness and sustainable behaviors in young learners. Future studies should expand respondent diversity and include additional features, such as varied challenges and adjustable difficulty levels, to further enhance educational outcomes.